Outcome of acute myocardial infarction versus stable coronary artery disease patients treated with coronary bypass surgery - Malmberg Markus; Gunn Jarmo; Rautava Päivi; Sipilä Jussi; Kytö Ville (TAYLOR & FRANCIS LTD, 2022)
Objective
To study the long-term outcome differences between acute myocardial infarction (MI) and stable coronary artery disease (CAD) patients treated with coronary artery bypass grafting (CABG).
Methods
We studied retrospectively patients with MI (n = 1882) or stable CAD (n = 13117) treated with isolated CABG between 2004 and 2014. Inverse propensity probability weight adjustment for baseline features was used. Median follow-up was 7.9 years.
Results
In-hospital mortality (8.6% vs. 1.6%; OR 5.94;p < .0001) and re-sternotomy (5.5% vs. 2.7%; OR 2.07;p < .0001) were more common in MI patients compared to stable CAD patients. Hospital surviving MI patients had higher all-cause mortality (28.2% vs. 22.2%; HR 1.37;p = .002) and MACE rate (34.4% vs. 27.4%; HR 1.22; CI 1.00-1.50;p = .049) at 10-year follow-up. Cardiovascular mortality (15.9% vs. 12.7%; HR 1.36;p = .017) and rate of new myocardial infarction (12.0% vs. 9.8%; HR 1.40;p = .034) were also higher in MI patients during follow-up. In follow-up of stabilized first-year survivors, the difference in all-cause (26.5% vs. 20.7%; HR 1.40;p = .003) and cardiovascular (14.2% vs. 11.4%; HR 1.37;p = .027) mortality continued to increase between MI and stable CAD patients.
Conclusion
MI patients have poorer short- and long-term outcomes compared to stable CAD patients after CABG and risk difference continues to increase with time.
Key Messages Patients with myocardial infarction have poorer short- and long-term outcomes compared to stable coronary artery disease patients after coronary artery bypass grafting (CABG). Higher risk of death continues also in stabilized first-year myocardial infarct survivors. The importance of efficient secondary prevention and follow-up highlights in post-myocardial infarct population after CABG.